Answer:
For this we can first multiply both sides by dx:
[tex]dy = 4x^{1/6}dx[/tex]
Next we can integrate both sides:
[tex]\int dy = \int 4x^{1/6}dx\\[/tex]
We can then solve both integrals to get:
[tex]y = 4(\frac{6}{7}x^{\frac{7}{6}}+C_1) = \frac{24}{7}x^{\frac{7}{6}}+C_2[/tex]
We can just say the constant is C2. So the answer is
[tex]y = \frac{24}{7}x^{\frac{7}{6}}+C_2[/tex]
We can also check this by differentiating both sides. We will ultimately get the equation we with. If I made any mistakes or misread something, please let me know.